PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HW HOTEL PADANG - Supa, Rahmi Dera (RC-INSTITUT, 2019)
This study aims to determine the effect of work motivation on employee work productivity at HW Hotel Padang. The type of research conducted in this study is a quantitative descriptive research using causative associative methods. The population in this study were all employees at HW Hotel Padang. The sampling technique in this study was a saturated sample with a sample of 45 employees. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. Technical analysis uses the help of the SPSS Computer Program version 16.00. The results of the study show: 1) The work motivation in HW Padang Hotel is at an average score of 56% with a fairly good category, 2) The work productivity of employees at HW Hotel Padang is at an average score of 89% with very good categories, 3) Results Person Product Moment correlation shows that there is a positive and significant influence between work motivation and work productivity of employees at HW Padang Hotel, with the results of linear regression testing obtained F value of 10.435 with significant 0.002 <0.05, which means variables X and Y are significant. Then the work motivation variable influences employee work productivity variables, so Ha is accepted and Ho is rejected.The value of R square in this study amounted to 0.195 this means that the variable Employee Motivation has an effect of 19.5% on Employee Productivity at HW Hotel Padang and 80.5% is influenced by other variables